The Effect of Entrepreneurial Knowledge on the Third Age Entrepreneurial Intention - Yusuf, Lamidi; Muhammed, Abdulrahman (2017)
The retirement income is not large enough to satisfy Nigerian’s expectations for a better standard of living upon retirement, a phenomenon that made most retirees to experience painful declines in their standard of living after retirement leading to various socio-economic challenges for the retirees, thus, this study examines the effect of entrepreneurial knowledge in inducing the third age entrepreneurial intention.Using Stratified sampling method, 176 retired federal workers that attended the mandatory pre-retirement entrepreneurial training programmes which cut across the military, para military and civil retirees residing in Kwara and Kogi states of Nigeria were used for this study through self-administered questionnaires. The Partial Least Square-Structural Equation Model was employed to test the hypothesis.The result suggests a positive and significant relationship between entrepreneurial knowledge and entrepreneurial intention among the third age entrepreneurs, suggesting that entrepreneurial knowledge can simulate intention towards a later career in entrepreneurship among the retirees. However, it is found that despite the individual entrepreneurial intention and the decision to continue their labour force upon retirement, through entrepreneurship, most retirees still continue to remain doing nothing and jobless due to lack of financial capital, non-access to information and unfriendly government regulation. The study recommends that retiring individuals must embrace retirement planning through participation in cooperative society and involvement in early saving for retirement. In addition, Individuals should be encouraged to start business few years before retirement age to gain foundation necessary for business experience.